Fully recyclable and high-performance carbon fiber composites based on thermoplastic epoxy polymer. (November 2022) - Chen, Duo; Li, Juanzi; Yin, Wenxuan; Yuan, Yuhuan; Cui, Yunguang; Li, Shichao; Liu, Minjing; Peng, Cong; Liu, Xin; Ye, Jinrui; Wu, Zhanjun
Abstract: In this paper, a linear and highly polymerized thermoplastic epoxy (TPE) is treated as the matrix to prepare the fully recyclable and high performance carbon fiber reinforced TPE composites (CFRTPE). The TPE is synthesized from bisphenol A epoxy and aniline through a simple polymerization process, whose mechanical and thermal properties (tensile strength: 65 MPa, tensile modulus: 2.3 GPa, initial decomposition temperature: 365.4  °C ) are comparable to that of traditional bisphenol A epoxy based thermoset. The CFRTPE composites samples could be prepared by prepreg through molding and vacuum bag method with the mild conditions (180  °C for 20 min). The mechanical and thermomechanical properties testing results show that the CFRTPE could achieve comparable and even better mechanical performance compared with the reference specimen and literature reports. Most importantly, both the full-length CFs and TPE of CFRTPE composites could be recycled conveniently and rapidly at room temperature without damaging the morphologies and mechanical properties, which indicates promising potential for practical applications. Graphical abstract: The epoxy based thermoplastic polymer can be treated as matrix to prepare the high performance and fully recyclable carbon fiber composites. Image 1 Highlights: Highly polymerized thermoplastic epoxy (TPE) was obtained from epoxy and aniline. CF-reinforced TPE (CFRTPE) could be fabricated under mild molding conditions. CFRTPE composites exhibit excellent mechanical and thermomechanical properties. Full-length CFs and matrix of CFRTPE could be rapidly recycled at room temperature.